"Sponge City" in China—A breakthrough of planning and flood risk management in the urban context. (July 2018) - Chan, Faith Ka Shun; Griffiths, James A.; Higgitt, David; Xu, Shuyang; Zhu, Fangfang; Tang, Yu-Ting; Xu, Yuyao; Thorne, Colin R.
Highlights: In 2014, the "Sponge City" concept initiated in ∙China that aims to tackle urban water issues include surface water floods. This viewpoint paper aims to explicate the "Sponge City" concept and implications to land-use planning and water management practice. This paper offers recommendations for a better deliver of "Sponge City" practices. We also indicated some upcoming opportunities and challenges on urban planning and water management issues in Chinese cities. Abstract: Surface water flooding is currently viewed as the most serious water-related issue in many of the China's large cities due to rapid urbanization, land-use change and the process of rapid socio-economic development. In 2014, the People's Republic of China established the concept of the 'Sponge City', which will be used to tackle urban surface-water flooding and related urban water management issues, such as purification of urban runoff, attenuation of peak run-off and water conservation. The concept is being developed to make use of 'blue' and 'green' spaces in the urban environment for stormwater management and control. It is envisaged that related practices will enhance natural ecosystems and provide more aesthetically pleasing space for the people that live and work in urban environments, in addition enabling nature-based solutions to improve urban habitats for birds and other organisms. Until recently, grey infrastructure and hard engineering-based management approaches have been adopted in the rapidly developing Chinese urban environment as urban flood and drainage issues are predominantly managed by municipal water engineers. The Sponge City concept and related guidelines and practices will provide multiple opportunities to integrate ideas from eco-hydrology, climate change impact assessment and planning, and consideration of long-term social and environmental well-being, within the urban land-use planning process. This paper aims to explicate the Sponge city concept and its development, and consider the implications of the transformation of urban land-use planning and urban-water management practice in China. To achieve the dual goals of sustainable water-use and better flood control (as targeted by the Sponge City concept), more effective development and implementation of land-use guidance and assessment tools (with explicit integration of urban flood-risk assessment, land-drainage guidance, climate projection methods, and assessment of long-term sustainability) are recommended.